Balancing the benefits of ecotourism and development: The effects of visitor trail-use on mammals in a Protected Area in rapidly developing China - Zhou, Y; Buesching, C; Newman, C; Kaneko, Y; Xie, Z; Macdonald, D (2013)
Despite economic benefits, particularly in developing countries, ecotourism can have unintended negative consequences for wildlife conservation in protected areas (PAs). We report the effects of tourist Trail-Type and -. Use on the incidence of mammal fieldsigns in a PA in central China. Surveys conducted adjacent to five categories of trail-type and fieldsigns were scored for three duplicates of four 0.5. km transects (=60 transects). Higher Trail Use along more major Trail Types were associated with significantly fewer fieldsigns along transects close to trails, compared with more distant transects. Fieldsign scores along transects adjacent to less used, unpaved trails were far less affected. In multiple-regression models, species and guilds exhibited different fieldsign score responses to Trail Type and Use. In general, a paucity of larger mammal (>15. kg) fieldsigns was associated primarily with greater Trail Use, whereas fieldsign scores for smaller mammals were associated more strongly with human-modified forest types. As international demand for nature-based tourism continues to grow it is important to evaluate openly the consequences of providing public access to protected areas while conserving biodiversity. © 2013 Elsevier Ltd.